La sexualité à l'épreuve de la médicalisation : le Viagra - Bajos, Nathalie; Bozon, Michel (Actes de la recherche en sciences sociales, 1999)
Les AA. analysent l'impact du Viagra sur l'evolution des comportements sexuels. Ils distinguent les dysfonctionnements sexuels d'origine organiques et les troubles de l'activite sexuelle lies a des facteurs psychologiques comme le stress. Ils soulignent que le Viagra apparait comme un remede a la defaillance sexuelle. Ils s'efforcent d'evaluer l'impact de la mise sur le marche de ce medicament. Ils mettent en garde contre le risque de renforcement de la norme «erectocentrique», contre le risque d'appauvrissement concomitant du jeu erotique et contre le risque de dependance vis-a-vis du Viagra.
Keywords: 1900-1999; 1980-1989; 1990-1999; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexualité; inégalités; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Culture, society and sexuality: a reader - Parker, Richard G.; Aggleton, Peter (Social aspects of AIDS, 1999)
Since the beginnings of time, people have been interested in sex - the form it takes, the pleasure it can give, the circumstances in which it occurs, and what it means - both for the individuals concerned and to society more generally. Often seen as a synonym for love, sometimes as an expression of power, and infrequently as a means of exploitation and abuse, sex is a complex and multi-faceted aspect of human behaviour that has been written about by numerous writers and theorists worldwide. This book offers an introduction to the central debates in sexuality research. Among the issues examined are the social and cultural dimensions of sex, human sexuality and sex research. It will be of use to students of sociology, cultural studies, and health and behavioural studies.
Keywords: LGBTQIA2+; VIH; approches et analyses; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques